The accuracy of the 1-hour typhidot test as a diagnostic tool for typhoid fever among filipinos - Butac, Charity Ann Ypil
Objective: To determine the validity of the Typhidot test in the diagnosis of typhoid fever with blood culture as the gold standard. Correct diagnosis is crucial in the proper management of typhoid fever and in the prevention and control of the spread of the disease. Delay in initiating effective therapy could lead to a higher incidence of life-threatening complications, prolonged hospitalizations and increased mortality. Hence, there is a clear need for a sensitive, specific and inexpensive test that will permit rapid diagnosis of the disease. Design: A cross-sectional, validity criterion-standard study wherein the Typhidot test was evaluated through an independent and blind comparison with blood culture as the gold standard. Setting: The study was conducted in local health centers, private clinics, secondary and tertiary private and government hospitals and government hospitals and communities in Cebu and Leyte, including areas with typhoid outbreaks namely: Aragao, Cebu; Carmen, Cebu; and Baybay, Cebu. Participants: Three hundred seventeen (317) consecutive typhoid suspects who sought consultation or admission in local health centers, clinics and hospitals from the period July 1, 1998 to January 31, 2000 who satisfied the following criteria were included in this study: Inclusion criteria: 1) moderate to high grade fever (<38.5 C) for > 5 days 2) with clinical manifestations suggestive of typhoid fever; at least five of the following should be present: chills, body malaise/myalgia, cough, headache, abdominal pain/discomfort/tenderness, anorexia, vomiting/nausea, diarrhea/constipation, relative bradycardia, hepatomegaly/splenomegaly, hematochezia/melena, mental confusion/delirium 3) written informed consent. Exclusion criteria: history of typhoid immunization, severe malnutrition, immunocompromised patients. Main Outcome Measures: The validity of the Typhidot test was evaluated by determining the sensitivity, specificity, positive and negative likellihood ratios. These properties were estimated at a 95% confidence level. The positive and negative predictive values were also calculated. Results: Patients were categorized into three groups, namely: Group 1=typhoid fever casesw (culture positive)- 199 patients (62.8%), Group 2 = typhoid fever cases (clinical diagnosis) - 74 patients (23.3%) and Group 3 = Non typhoid cases - 44 patients (13.9%). Group 1 (blood-culture positive cases) was compared to Groups 2 and 3 (blood-culture negative cases) to determine Typhidot test properties using blood culture as the gold standard. Typhidot test has a sensitivity of 93% (95% CI: 88-96), specificity of 64% (95% CI: 55 - 73), positive predictive value of 82%, negative predictive value of 84%, positive likelihood ratio of 2.6 (95% CI: 2.1 - 3.4) and negative likelihood ratio of 0.11 (95% CI: 0.06 - 0.18). A sensitivity analysis was done wherein Groups 1 and 2 (Typhoid fever cases) were compared to Group 3 (Non-typhoid cases). With clinical diagnosis as the gold standard, the Typhidot test has a sensitivity of 82% (95% CI: 77 - 87), specificity of 96% (95% CI: 83 - 99), positive predictive value of 99%, negative predictive value of 47%, positive likelihood ration of 18.1 (95% CI: 5.4 - 65.7) and negative likelihood ratio of 0.18 (95% CI: 0.14 - 0.24). A subgroup analysis according to history of antibiotic intake shoswed the following test properties among typhoid suspects with prior antibiotic intake: sensitivity of 96%, specificity of 63%, positive predictive value of 80%, negative predictive value of 90%, positive likelihood ratio of 2.6 and negative likelihood ratio of 0.07. Among typhoid suspects without prior antibiotic intake, Typhidot test has a sensitivity of 89%, specificity of 68%, positive predictive value of 86%, negative predictive value of 74%, positive likelihood ratio of 2.8 and negative likelihood ratio of 0.61. Conclusion & Recommendation: Based on the aforementioned test properties, Typhidot test is accurate enough to detect typhoid fever in lieu of the more expensive and more time-consuming blood culture. This would facilitate earlier diagnosis of typhoid fever resulting in more prompt management, thus preventing the sequelae of such disease. Moreover, because of the added advantage of the simplicity of theprocedure, it would be very useful in hospitals with no ulture facilities and in the field especially during outbreaks.
Theses--(Master in Science in Epidemiology-Clinical Epidemiology) UPCM
Keywords: Typhoid Fever